NAZHARIYAH AL-'AMIL WA TADLAFUR AL-QARA'IN INDA TAMMAM HASAN - Luthfi, Taufik (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2016)
The researcher attempts to identify the thoughts of Tamman Hassan concerning Tadhafur Al-Qarain and Amil theories in Arabic language grammar. This research is qualitative descriptive research. The data of this reseach based on Tamman Hassan’s legacy concerning the subject of tadhafur al-qarain. This study is based upon two main subjects, namely analysis of the content of the book and compares with the thoughts of other scholars. The study concluded that the new concept devised by Tammam Hassan called tadhafur al-qarain theory. This theory rejects the concept of ‘amil from classic grammar experts in grammatical analysis and understanding of Arabic texts. Tammam Hassan then replaces the concept of ‘amil, by analysis of the link between ma’na and mabna.DOI : 10.15408/a.v3i1.2911